Monitoring agricultural productivity for sustainable production and R&D planning - Laborde Debucquet, David; Piñeiro, Valeria (Kiel Institute for the World Economy, 2018)
Argentina’s G20 presidency has emphasized the need to improve soil management and sustainably increase agricultural productivity to achieve an inclusive and resilient food future. While increased agricultural productivity can improve economic welfare and help address food security problems by benefiting both consumers and producers simultaneously, it also must address the depletion of already scarce natural resources. In the context of a changing climate, sustainable and resilient agricultural production forms a major cornerstone of both adaptation and mitigation strategies. The global community needs to have the proper tools with which to monitor sustainable agricultural productivity gains, identify countries and sectors lagging behind, and commit R&D efforts accordingly to address the challenges ahead. As such, it is suggested that 1) an international consortium should monitor agricultural total factor productivity (TFP) to provide international comparisons and track performance over time; 2) the G20 should acknowledge and address the issue of sustainable productivity measurement, and; 3) the G20 should support more in-depth research into the relationship between agricultural TFP and agricultural R&D.